Formation and properties of strontium zinc pyrophosphate - Gorodylova, Nataliia; Dohnalová, Žaneta; Šulcová, Petra (University of Pardubice, 2014)
In present research we focused on the synthesis and investigation of properties of double strontium(II) zinc(II) phosphate — SrZnP2O7. Different synthesis approaches, including solid state reaction and coprecipitation, as well as different experimental conditions (initial reagents and homogenisation route) were used for the preparation of SrZnP2O7. The reaction route between the initial reagents was followed using DTA/TG and XRD methods. The obtained powders were characterised by IR spectroscopy and their thermal stability was followed by heating microscopy. Focusing on pigmentary application, specific properties of the samples were evaluated such as particle size distribution, colour parameters, and also preliminary anticorrosion tests were performed.